Imperial Hunting or Pleasure House, in the Prater, near Vienna - Prixner, Gottfried, 1746-1819 (engraver):::Creator:::::::::::: (Austria; Vienna; R. Sammer, 2020)
Engraving of the Imperial Hunting or Pleasure House, in the Prater, near Vienna